Pineapple peel biochar and lateritic soil as adsorbents for recovery of ammonium nitrogen from human urine. (1st September 2021) - Otieno, Austine O.; Home, Patrick G.; Raude, James M.; Murunga, Sylvia I.; Ngumba, Elijah; Ojwang, Dickson O.; Tuhkanen, Tuula
Abstract: Human urine is a rich source of nitrogen which can be captured to supplement the existing sources of nitrogen fertilizers thus contributing to enhanced crop production. However, urine is the major contributor of macronutrients in municipal wastewater flows resulting into eutrophication of the receiving water bodies. Herein, pineapple peel biochar (PPB), and lateritic soil (LS) adsorbents were prepared for the safe removal of ammonium nitrogen (NH4 + -N) from human urine solutions. Physicochemical properties of PPB, and LS were characterized by scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS), X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA) to investigate the relationship of their properties with NH4 + -N adsorption. Langmuir, Freundlich, and Dubinin-Radushkevich (D-R) isotherm models were employed to correlate the experimental equilibrium adsorption data. The effect of contact time and initial concentration of NH4 + -N adsorption was also evaluated. The D-R isotherm model best described the behaviour of NH4 + -N adsorption on both PPB and LS based on the coefficient of correlation values. This model showed that the adsorption of NH4 + -N on both samples was a physical process with PPB and LS having mean surface adsorption energies of 1.826 × 10 −2, and 1.622 × 10 −2  kJ/mol, respectively. The PPB exhibited a slightly higher adsorption capacity for NH4 + -N (13.40 mg/g) than LS (10.73 mg/g) with the difference attributed to its higher surface area and porosity. These values are good indicators for assessing the effectiveness of the materials for adsorption of NH4 + -N from human urine. Graphical abstract: Image 1 Highlights: Pineapple peel biochar had higher adsorption capacity for NH4 + -N from human urine. NH4 + -N adsorption from human urine followed Dubinin-Radushkevich (D-R) model. Physisorption was the major NH4 + -N adsorption mechanism from human urine. Acidic functional groups, surface area and porosity enhanced adsorption of NH4 + -N. Increasing contact time and initial concentration increased NH4 + -N adsorption.